Differential Effects of Adiposity and Childhood Growth Trajectories on Retinal Microvascular Architecture. (12th October 2013) - Tapp, Robyn J.; Ness, Andrew; Williams, Cathy; Howe, Laura D.; Tilling, Kate; Witt, Nicholas; Chaturvedi, Nish; McG Thom, Simon A.; Hughes, Alun D.
Abstract Objectives We hypothesized that trajectories of adiposity across childhood would be associated with retinal microcirculatory diameters at age 12 years, independent of BP. Methods The ALSPAC followed a cohort of children born in 1991–1992. The current study includes all children with retinal images acquired at the 12 years clinic and individual trajectories of PI from 0 to 2 years and BMI from 2 to 10 years. Retinal microvascular measures included retinal arteriolar and venular diameters. Results Children in this analysis had a birth weight of 3.5 ± 0.4 kg, a PI of 26.2 ± 2.4 kg/m3 and a gestational age of 39.7 ± 1.4 weeks (mean ± SD). Analysis of growth trajectories showed that lower PI at birth was associated with narrower retinal arterioles. Higher PI at birth was associated with wider venular diameter, and a stronger positive association was evident between BMI change at 5–5.5 and 8.5–10 years with wider venular diameters. Current fat mass was also associated with wider venular diameters. Conclusions Retinal arterioles and venules are differentially associated with growth in early life and childhood adiposity. Early adiposity may adversely affect the microcirculation, with important implications for cardiovascular risk in adulthood.